1991
DOI: 10.1148/radiology.180.3.1871303
|View full text |Cite
|
Sign up to set email alerts
|

Steatocystoma multiplex: appearance at mammography.

Abstract: The authors present mammographic findings in a patient with steatocystoma multiplex. Numerous oil cysts were seen in both breasts at mammography. The mammographic appearance is characteristic of, if not pathognomonic for, steatocystoma multiplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…In our study, the lesions varied in color from fleshy to yellow [1,[6][7][8][9]. The more superficial lesions were yellow and prominent; deeper lesions were not visible and were skin-colored [8].…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In our study, the lesions varied in color from fleshy to yellow [1,[6][7][8][9]. The more superficial lesions were yellow and prominent; deeper lesions were not visible and were skin-colored [8].…”
Section: Discussionmentioning
confidence: 58%
“…Steatocystoma multiplex is a rare familial hamartomatous malformation of the piloseba- ceous duct junction that is characterized by the presence of multiple intradermal cysts that usually appear during adolescence and then progress [1,[5][6][7][8][9]. Although both sexes are equally affected, some authors have reported a greater prevalence in males [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations